Research on dual-output port on-board charging system based on CLLC resonant converter. - Kai Zhou; Hao Song; Ningzhi Jin; Dongyang Sun (PLoS ONE, 2023)
This paper proposes a dual-output port on-board charging system based on a CLLC resonant converter, which can realize the function of simultaneously charging high-voltage power batteries and low-voltage batteries. The system topology is composed of a front-stage PFC and a latter-stage CLLC resonant converter. The system uses a three-port transformer to couple the resonant converter, the high-voltage charging circuit, and the low-voltage charging circuit. The system also realizes soft switching through resonant components. According to the design requirements of the charging system, the control strategy of the dual-output ports is determined by analyzing the working mode and gain characteristics of the system and the dual closed-loop control structure is designed to realize the functions of power factor correction and wide-range voltage regulation. Simulation and experimental results verify the correctness of theoretical analysis and structural design.